Proton therapy for isolated local regional recurrence of breast cancer after mastectomy alone - Laughlin, Brady S.; Bhangoo, Ronik S.; Niska, Joshua R.; Thorpe, Cameron S.; Girardo, Marlene E.; Anderson, Justin D.; Kosiorek, Heidi E.; McGee, Lisa A.; Hartsell, William F.; Chang, John H.; Rossi, Carl J.; Tsai, Henry K.; et al. (Frontiers in Oncology, 2022)
Abstract Purpose/Objectives: To assess adverse events (AEs) and disease-specific outcomes after proton therapy for isolated local regional recurrence (LRR) of breast cancer after mastectomy without prior radiotherapy (RT). Materials/Methods: Patients were identified from a multi-institutional prospective registry and included if diagnosed with invasive breast cancer, initially underwent mastectomy without adjuvant RT, experienced an LRR, and subsequently underwent salvage treatment including proton therapy. Follow-up and cancer outcomes were measured from date of RT completion. Results: Nineteen patients were included. Seventeen patients were treated with proton therapy to the chest wall and comprehensive regional lymphatics (17/19, 90%). Maximum grade AE was grade 2 in 13 (69%) patients and grade 3 in 4 (21%) patients. All patients with grade 3 AE received > 60 GyE (p=0.04, Spearman correlation coefficient=0.5). At last follow-up, 90% of patients were alive with no LRR or distant recurrence. Conclusions: For breast cancer patients with isolated LRR after initial mastectomy without adjuvant RT, proton therapy is well-tolerated in the salvage setting with excellent local regional control. All grade 3 AEs occurred in patients receiving > 60 GyE.